Neurocognitive Predictors of Academic Outcomes among Childhood Leukemia Survivors - (Ki) Moore, Ida M. (Cancer Nurs, 2016)
BACKGROUND: Acute lymphoblastic leukemia (ALL) is the most common pediatric cancer and survival approaches 90%. ALL survivors are more likely than healthy peers or siblings to experience academic underachievement yet little is known about neurocognitive predictors of academic outcomes. OBJECTIVE: Objectives were to compare neurocognitive abilities to age-adjusted standardized norms; to examine change over time in neurocognitive abilities; and to establish neurocognitive predictors of academic outcomes. METHODS: Seventy-one children were followed over the course of therapy. Cognitive abilities were assessed during Induction when the child was in remission (Baseline) and annually for 3 years (Year 1, Year 2, Year 3). Reading and mathematics abilities were assessed at Year 3. RESULTS: Fine motor dexterity was significantly below age-adjusted norms at all data points, but showed improvement over time. Baseline visual-motor integration was within the normal range but significantly declined by Year 3, and mean scores at Years 2 and 3 were significantly below age-adjusted norms. Verbal short-term memory was significantly below age-adjusted norms at all assessments. Visual-motor integration predicted reading and mathematic abilities. Verbal short-term memory predicted reading abilities, and visual short-term memory predicted mathematic abilities. CONCLUSIONS: CNS-directed therapy is associated with specific neurocognitive problems. Visual spatial skills, verbal and visual short term memory predict academic outcomes. IMPLICATIONS FOR PRACTICE: Early assessment of visual spatial perception and short-term memory can identify children at risk for academic problems. Children who are at risk for academic problems could benefit from a school based Individual Educational Program and/or educational intervention.